Unilateral Obstructive Emphysema in Infancy due to Mediastinal Bronchogenic Cyst-Diagnostic Challenge and Management - Leena Robinson Vimala; Ravi Kishore Barla Sri Sathya; Arul Premanand Lionel; Jeenapalli Srinivasa Kishore; Kirubakaran Navamani (Journal of Clinical and Diagnostic Research, 2015)
Bronchogenic cysts are the most common cystic mediastinal lesion in children. Bronchogenic cyst causing unilateral obstructive emphysema is a rare presentation. We report the case of a one and half month old infant who presented with respiratory distress which was initially suspected as left pneumothorax on frontal chest radiograph but was later found to be due to hyperinflated left lung and hence the possibility of congenital lobar emphysema was considered. CT thorax and limited MRI sections revealed a cystic lesion in mediastinum causing obstructive emphysema and mediastinal displacement. He underwent an emergency thoracotomy and excision of the cyst via an extrapleural approach. Post operatively, rapid improvement of the infant was noticed both clinically as well as radiologically. Cross sectional imaging like CT or MR is required for reaching the correct and early diagnosis in paediatric patients with respiratory distress, when there is diagnostic dilemma based on chest radiograph.